Axiological Aspect of P. Dovydaitis’ Views on Scientific Cognition - Balčius, Jonas (Problemos, 1979)
P. Dovydaitis (1886-1942), a philosopher, neo-Thomist of bourgeois Lithuania, was one who identified scientific and religious cognition of the world. In his opinion, it is scientific knowledge and faith that mutually supplement each other with a profound, truly scientific and philosophical content. The neo-Thomist comes to the conclusion that the difference between scientific and religious cognition of the world lies just in the axiomatic orientation of man taking personal interest in this cognition.